Field experimental study on stratum classification of marine engineering based on cone penetration test - Xiangyang, H.; Lehan, T.; Gengsheng, Y.; Cheng, Z.; Ming, Z. (Frontiers in Materials, 2025)
This study focuses on the intertidal wind farm in Rudong, Jiangsu Province, and aims to enhance the accuracy of marine stratum classification using cone penetration test (CPT) technology. In situ CPT experiments were conducted with a 20 T double-bridge penetration tester to obtain parameters such as cone tip resistance and sleeve friction, and the raw data were optimized through wavelet denoising. The Robertson soil classification method was then applied to calculate the soil behavior type index and achieve continuous, high-resolution identification of seabed strata. The results show that the processed CPT data effectively identify thin layers, interlayers, and interbedded strata in complex marine sediments, revealing clear vertical variation patterns in sediment properties. Overall, the CPT-based stratigraphic classification approach demonstrates clear conceptual logic, operational simplicity, and strong repeatability, providing reliable technical support for foundation investigation, pile design, and engineering evaluation of offshore wind farms.